Pemanfaatan Pojok Baca atau Reading Corner dalam Pembentukan Karakter Peserta Didik dalam Menumbuhkan Literasi di MI Al-Khoiriyyah 02 Semarang - Ikrimah Dwi Noviyasari; Mursid Mursid (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This research aims to determine the activities in utilizing reading corners in forming the character of students in cultivating literacy at MI Al-Khoiriyah 02 Semarang. This research uses interview techniques, observation techniques and documentation retrieval techniques. This research uses a qualitative method which is supported by studies of scientific articles that are similar to the title. The study of scientific articles is to compare previous studies and find out information about research, determine problem topics, formulate problems and also record information from scientific articles. which is relevant. The purpose of this writing is to find out the use of reading corners which are carried out 5 minutes before Teaching and Learning Activities (KBM) take place, and to find out what impacts they have in improving character education on student literacy. and how the teacher educates so that character education is realized in the madrasa.